Equally different? Comparison of female and male rhetoric in political discourse - Kišiček, Gabrijela (Array, 2009)
The main purpose of this research was to find some specific differences between public speaking performed by male and female politicians. Numerous linguistic researches have discovered many differences between male and female talk (Lakoff 1975, Johnson 1996, Hall & Langellier 1988. etc.). It is general stereotyped belief that women have emotional approach and use emotional reasons to prove or explain their theses unlike men who are rational and use logical arguments in their public appearances (this stereotype was also investigated). Research was aimed to investigate this belief using the rhetorical analysis (logical fallacies, argumentation, rhetorical design and speech style) based on books of Weston (1992), Schopenhauer (2002), Fahenstock 1990), Toulmin (1969), Strong (1996), Freely (1996), Gronbeck (1995), Jaffe (1998), Marsh (1983) ect. Rhetorical analysis and answers of evaluators have shown that argumentation and rhetorical design of speech are different (in types and frequency of some arguments and logical fallacies) between female and male politicians but on the other hand discovered some rhetorical features specific for political discourse (both for female and male politicians).